Complex ownership and capital structure - Paligorova, Teodora; Xu, Zhaoxia (Journal of Corporate Finance, 2012)
This paper explores pyramidal firms and their motivations for the use of debt financing. We find that pyramids have significantly higher leverage than non-pyramids and that the use of debt in pyramids is associated with the risk of expropriation. We do not find evidence for the control-enhancing, disciplining, tax-reduction, and risk-sharing explanations for the use of debt financing. Our results indicate that the capital structure of pyramids is affected by the expropriation activities of ultimate owners that have excess control rights.